A Study of the Role and Approach of China English in the Spread of Chinese Culture Based on the Analysis of Big Data. Issue 4 (February 2021) - Zhang, Yuling
Abstract: In the face of the 21st century, the spread of culture and knowledge is a trend and necessity through the presentation of big data all over the world. China English shoulders the important mission of introducing, disseminating and promoting Chinese culture to the world. As an important medium, it plays an important role in the construction of Chinese cultural identity. We should be aware of the trend integration of global culture in the new era, more clearly aware of the severe challenges brought by the exchange and confrontation of different cultures to the weak culture. While introducing and learning western culture, we must try our best to inherit and carry forward the profound traditional culture of the Chinese nation, and call on our traditional culture to spread out.